VET Realignment and the Development of Technical Elites: Learning at Work in England - Esmond, Bill; Atkins, Liz (International Journal for Research in Vocational Education and Training, 2020)
Context: An enhanced role for work-based learning is advocated increasingly widely across industrialised countries and by international Vocational Education and Training (VET) policies. However, this is framed differently in each country by long-term policy orientations that reflect VET’s relationship with wider economic and social formations. These national differences reflect path dependency but also distinctive responses to contemporary challenges such as globalisation. In England, recent reforms strengthening workplace learning are constrained by existing patterns of skill formation and may be shaped by further market liberalisation and divergence from social and economic policies in Europe. Approach: The study examined the relationship between greater emphasis on workplace learning in England and societal change, addressing the research question: how are early experiences of work in England, as part of young people’s full-time education programmes, positioning them for future employment? Case studies were organised around apparently distinctive placement types that had emerged from earlier studies. Using the constant comparative method, the team identified a series of categories to distinguish the way each type of work-based learning positioned students in a particular type of labour market transition. Findings: Evidence emerged of divergence in England’s "further education" system, across mainly male "technical" routes, young people on vocational courses preparing them for routine, low-skilled, precarious employment, and an area of greater uncertainty preparing young people for digital routes linked to the "new economy". Key dimensions of difference included study locations, discourses of occupational status, types of valued learning content, approaches to socialisation, sources of expertise and processes of credentialisation. In each case, learning at work served to position students for a particular type of labour market transition, which we characterise as technical elite formation, welfare VET and new economy precarity. Conclusion: Approaches to workplace learning in England already reflect social distinctions but entail the possibility of reinforcing these, supporting a more hierarchical pattern of labour market transition. Whilst the upper strata of VET shift their purpose to support the formation of new "technical elites", others face the possibility of further marginalisation. Such new inequalities could become central to a further fragmented society in a post-Brexit, post-COVID-19 Britain. Other European states facing challenges of globalisation and the transition to services are also likely to experience pressures for VET stratification, although they may seek less divisive solutions.